Using personalized 3D printed Titanium sleeve-prosthetic composite for reconstruction of severe segmental bone loss of proximal femur in revision total hip arthroplasty: A case report - Wang, Xingshan (Medicine (Baltimore), 2020)
RATIONALE: Allograft-prosthetic composites (APCs) and proximal femoral replacement have been applied for reconstruction of severe segmental femoral bone loss in revision total hip arthroplasty. The outcomes are encouraging but the complication rate is relatively high. Considering the high complication rates and mixed results of APCs and megaprosthesis, we presented a case using personalized 3D printed Titanium sleeve-prosthetic composite for reconstruction of segmental bone defect. PATIENT CONCERNS: A 73-year-old woman presented to the emergency department on account of acute severe pain of the left hip without history of trauma. She had undergone a cemented total hip arthroplasty for osteonecrosis of femoral head at the left side in 2000. In 2013 she underwent a cemented revision total hip arthroplasty as a result of aseptic loosening of hip prosthesis. She denied obvious discomfort prior to this episode since the revision surgery in 2013. DIAGNOSIS: According to the clinical history, imaging and physical examination, we confirmed the diagnosis of severe segmental bone loss of proximal femur and fracture of prosthetic stem. The femoral bone defect was evaluated using the Paprosky classification system and rated as Type 3B, and the acetabular bone defect was rated as Type 2C. INTERVENTIONS: In this study, we present the first case of severe segmental bone loss of proximal femur in revision total hip arthroplasty that was successfully treated using personalized 3D printed Titanium sleeve-prosthetic composite OUTCOMES: At the 2-year follow-up, the patient was symptom free with a Harris Hip Score of 91. Radiographs showed excellent osteointegration between the interface of sleeve-prosthetic composite and the host bone, with no signs of implant loosening or subsidence. LESSONS: Despite the absence of long term results of 3D printed Titanium sleeve-prosthetic composite reconstruction, the good clinical and radiological outcome at 2 years follow up implied its potential role for reconstruction of segmental femoral bone defect in revision THA.